Caregiving with love and joy : an expert's guide to providing the best Alzheimer's disease and dementia home care - Boswell, Patricia A. (Avery, an imprint of Penguin Random House, 2022)
"When it comes to caring for a loved one with Alzheimer's disease or dementia, the right caregiving can make all the difference. Here, Patricia Boswell shares structured routines, life hacks, and best practices that are evidence-based and focused on maintaining the highest possible quality of life for the entire family. As a nurse and dementia expert, Boswell knows that the best caregivers think like a problem-solver, addressing physical and emotional issues as they come up. Whether readers are providing the care themselves, managing a caregiver, or sharing the responsibilities, this book presents the most effective tips, tricks, and small changes that can reduce stress and make life easier. This comprehensive guidebook will redefine the caregiving experience as one that can be life-affirming and enjoyable. It offers a singular resource for anyone who is looking to provide or manage outstanding daily care while maintaining--and even enhancing--their own health and mental well-being." -- Amazon.